Pemanfaatan AI Speech To Text untuk Menstimulasi Kemampuan Berbicara Anak Usia Dini: Utilization of AI Speech To Text to Stimulate Early Childhood Speaking Skills - Suci Rahmadani; Mohammad Salehudin (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
Speaking is a vital basic skill for early childhood, as it is the foundation for future communication and language development. In the digital era, technologies such as speech-to-text offer new opportunities to create interactive and visual-based learning experiences, thus supporting children in developing their speaking skills more effectively. This study aims to explore the use of speech-to-text technology in supporting children's speaking skills at Nurul Huda Palaran Kindergarten. The approach applied is descriptive qualitative, with sources designed through observation, interviews, and documentation to provide an in-depth understanding of the application of this technology in the learning process. The data analysis process follows three main stages adapted from Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The study shows that the application of speech-to-text technology has a positive impact on improving children's pronunciation, fluency, and vocabulary mastery. This technology provides direct feedback to children in the form of text from speech, which helps children recognize errors and correct them. However, several challenges were found, such as inaccurate transcription for certain pronunciations, which were successfully overcome through teacher assistance to provide further guidance. In conclusion, the integration of speech-to-text technology is an effective innovative approach to support the development of early childhood speaking skills. The success of implementing this technology is highly dependent on the combination of optimal use of technology and a humanistic approach by teachers to create a balanced learning experience.   ABSTRAK Berbicara adalah sebuah keterampilan dasar yang vital bagi anak usia dini, karena menjadi pondasi bagi perkembangan komunikasi dan bahasa dimasa depan. Dalam era digital, teknologi seperti speech-to-text menawarkan kesempatan baru untuk memunculkan pengalaman belajar yang interaktif dan berbasis visual, sehingga mendukung anak dalam mengembangkan kemampuan berbicara secara lebih efektif. Penelitian ini bertujuan untuk mengeksplorasi penggunaan teknologi speech-to-text dalam menunjang kecakapan berbicara anak di TK Nurul Huda Palaran. Pendekatan yang diterapkan adalah kualitatif deskriptif, dengan sumber yang dirancang melalui observasi, wawancara, dan dokumentasi untuk memberikan pemahaman mendalam tentang penerapan teknologi ini dalam proses pembelajaran. Proses analisis data mengikuti tiga tahap utama yang diadaptasi dari Miles dan Huberman, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Telaah menunjukkan bahwa penerapan teknologi speech-to-text memiliki dampak positif dalam meningkatkan aspek pelafalan, kelancaran berbicara, dan penguasaan kosakata anak. Teknologi ini memberikan umpan balik langsung kepada anak dalam bentuk teks dari ucapan, yang membantu anak mengenali kesalahan dan memperbaikinya. Meski demikian, ditemukan beberapa tantangan, seperti ketidakakuratan transkripsi untuk pelafalan tertentu, yang berhasil diatasi melalui pendampingan guru untuk memberikan bimbingan lebih lanjut. Kesimpulannya, integrasi teknologi speech-to-text merupakan pendekatan inovatif yang efektif untuk mendukung pengembangan kemampuan berbicara anak usia dini. Keberhasilan penerapan teknologi ini sangat bergantung pada kombinasi antara pemanfaatan teknologi secara optimal dan pendekatan humanistik oleh guru untuk menciptakan pengalaman belajar yang seimbang.